2009
DOI: 10.1007/s11356-009-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of phenanthrene by nanosized alumina coated with sequentially extracted humic acids

Abstract: Due to the high adsorption of HA on nano-Al(2)O(3) and its significant effect on phenanthrene sorption, interactions of NOM with nano-oxides and their mechanistic relations with NOM conformation changes and HOC sorption merit further research. In addition, due to the higher sorption of phenanthrene on the HA-coated nano-Al(2)O(3) than the pure counterpart, the effect of NOM and HOCs on the ecotoxicity of NPs should be addressed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…S1. The aromaticity of HA fraction decreased with increasing extraction, since the later extracted HA fraction had lower C/H ratio and SUVA 254 values which can identify the abundance of aromatic carbon of the HA fractions (Weishaar et al, 2003;Yang et al, 2010;Baken et al, 2011). The calculated aromaticity of HAA, HAB, HAC and HAD were 54%, 45%, 39% and 33%, respectively (Table S1).…”
Section: Characteristics Of Ha Fractionsmentioning
confidence: 96%
See 2 more Smart Citations
“…S1. The aromaticity of HA fraction decreased with increasing extraction, since the later extracted HA fraction had lower C/H ratio and SUVA 254 values which can identify the abundance of aromatic carbon of the HA fractions (Weishaar et al, 2003;Yang et al, 2010;Baken et al, 2011). The calculated aromaticity of HAA, HAB, HAC and HAD were 54%, 45%, 39% and 33%, respectively (Table S1).…”
Section: Characteristics Of Ha Fractionsmentioning
confidence: 96%
“…The polarity of HA fraction, defined as atomic ratio of (N + O)/C (Xing et al, 1994), also decreased from 0.49 for HAA to 0.38 for HAD (Table 1). However, the aliphaticity of HA fraction increased with increasing extraction, indicated by the lower O/C and (N + O)/C ratios in the later extracted HA fraction (Yang et al, 2010). The calculated aliphaticity of HAA, HAB, HAC and HAD were 46%, 55%, 61% and 67%, respectively (Table S1).…”
Section: Characteristics Of Ha Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After soils were contaminated by landfill leachate, certain functional groups of DOM could form complex with clay minerals owing to the fine particle size, favorable microspores, and high sorption capacity [8,9]. Thus, interactions of DOM from landfill leachate with clays could affect significantly the fate and reactivity of organic pollutants in soils [9,10], such as HOCs. Besides, one of the traditional liners is geosynthetic clay liners (GCLs), consisting primarily of nature clays or processed clays [11].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al also suggested that humic acids adsorption by nano-Al 2 O 3 could be basically explained with a ligand exchange mechanism because of the protonated OH 2 + groups on the Al 2 O 3 surface [10]. Besides, many works about pyrene sorption studies have been reported.…”
Section: Introductionmentioning
confidence: 99%